Processo de otimização aplicado em método descritivo da análise de dados - Gomes, Flávio Adalberto (2018)
This work presents methodology for construction and optimization of mathematical structures that represent experimental data. A hybrid optimization process between an heuristic method and a direct search deterministic method is used. Input and output values of real systems are used and some mathematical expressions are formulated to be used as test and validation. The results are compared with traditional methods, analyzing the oscillations at the edges. The proposed method presents a feasible solution for experimental data analysis and extrapolation, with reduced mathematical expressions.